2021
DOI: 10.3390/ijms22063227
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomic Analysis of Subcutaneous and Omental Adipose Tissue Reveals Increased Lipid Turnover in Dairy Cows Supplemented with Conjugated Linoleic Acid

Abstract: Phosphoproteomics is a cutting-edge technique that can be utilized to explore adipose tissue (AT) metabolism by quantifying the repertoire of phospho-peptides (PP) in AT. Dairy cows were supplemented with conjugated linoleic acid (CLA, n = 5) or a control diet (CON, n = 5) from 63 d prepartum to 63 d postpartum; cows were slaughtered at 63 d postpartum and AT was collected. We performed a quantitative phosphoproteomics analysis of subcutaneous (SC) and omental (OM) AT using nanoUPLC-MS/MS and examined the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 67 publications
(88 reference statements)
0
6
0
Order By: Relevance
“…As stated in previous studies, MS-based proteomics should strive to maintain accuracy within a range of 1.3- to 2-folds. Then, we chose the 1.5-fold change as an acceptable threshold of the statistically significant difference. …”
Section: Discussionmentioning
confidence: 99%
“…As stated in previous studies, MS-based proteomics should strive to maintain accuracy within a range of 1.3- to 2-folds. Then, we chose the 1.5-fold change as an acceptable threshold of the statistically significant difference. …”
Section: Discussionmentioning
confidence: 99%
“…In a comprehensive study with transition dairy cows, the effects of essential FAs (EFAs) and CLA on metabolic and inflammatory indices were examined; supplementation of a combination of EFAs and CLA improved the metabolic state of the cows, increased their energy balance, and had a moderate effect on hepatic acute phase proteins, while the effect of CLA alone on inflammatory markers was minor ( Gnott et al, 2020 ). The effects of CLA supplementation were also evaluated in adipose tissues and liver; in adipose tissues, it was found that CLA supplementation affected the integrated phosphoproteome toward phosphorylation of proteins related to lipolysis and lipogenesis ( Daddam et al, 2021 ). In the liver of cows supplemented with a combination of CLA and EFAs, the relative abundance of several proteins related to CYP450 epoxidation/hydroxylation was affected ( Veshkini et al, 2022 ), and this was proposed to be related to an immunometabolic effect of CLA, as CYPP450 regulates the cross-talk between the immune system and metabolism.…”
Section: Dietary Immunomodulators In Transition Dairy Cowsmentioning
confidence: 99%
“…Supplementation of CLA to transition dairy cows can also affect components of the ECS in the adipose tissue and uterus, which may be part of the immunometabolic effects of this FA. The expression of the enzyme diacylglycerol lipase A (DAGLA), which synthesizes the eCB 2-AG, was higher in adipose tissue of cows supplemented with CLA vs. controls, and the mRNA and protein abundances of CB1 were reduced in CLA supplemented cows ( Daddam et al, 2021 ). In addition, CLA supplementation to transition dairy cows reduced the expression of uterine CNR2/CB2 and NAPEPLD ( Abolghasemi et al, 2016 ).…”
Section: Dietary Immunomodulators In Transition Dairy Cowsmentioning
confidence: 99%
“…Using condensed tannins to increase dietary protein availability in low soybean meal lamb diets has shown promising results [9], whereas novel alternative feedstuffs such as microalgae are currently being tested [94]. Using proteomics to understand the physiological effects of such dietary alternatives has hence been successfully demonstrated [9,94].Recently, the use of phospho-proteomics has emerged as a new frontier in domestic animal research [95].…”
Section: Future Trends: Omics As a Tool For Animal And Veterinary Early-stage Researchersmentioning
confidence: 99%